Current status of brown planthopper (BPH) resistance and genetics - Jena, Kshirod K.; Kim, Suk-Man (Springer, 2010)
Among the planthoppers of rice, the brown planthopper (BPH) is a major threat to rice production and causes significant yield loss annually. Host-plant resistance is an important strategy to reduce the damage caused by BPH and increase rice productivity. Twenty-one major genes for BPH resistance have been identified by using standard evaluation methods developed at the International Rice Research Institute (IRRI) to distinguish resistance or susceptibility of rice genotypes to BPH biotypes/populations. These genes are from diverse genetic resources such as land race cultivars and wild species ofOryza. Of the 21 resistance genes, 18 genes have been localized on specific region of six rice chromosomes using molecular genetic analysis and genomics tools. Some of these resistance genes are clustered together such asBph1,bph2,Bph9,Bph10,Bph18, andBph21on the long arm of chromosome 12;Bph12,Bph15,Bph17andBph20on the short arm of chromosome 4;bph11andBph14on the long arm of chromosome 3 andBph13(t) andbph19on the short arm of chromosome 3. Six genes (Bph11,bph11,Bph12,bph12,Bph13andBph13) originated from wildOryzaspecies have either duplicate chromosome locations or wrong nomenclature. The discrepancy should be confirmed by allelism tests. Besides identification of major resistance genes, some quantitative trait loci (QTLs) associated with BPH resistance have also been identified on eight chromosomes. Most of the rice cultivars developed at IRRI possess one or two of the major resistance genes and the variety IR64 has many QTLs and confers strong resistance to BPH. More BPH resistance genes need to be identified from the wealth of gene pool available in the wild species ofOryza. Two BPH resistance genes (Bph14andBph18) have been cloned, and a snow drop lectin gene (GNA) has been identified and used in the development of BPH-resistant transgenic plants. Efficient introgression of resistance genes (Bph1,bph2,Bph3,Bph14,Bph15,Bph18,Bph20, andBph21) into elite rice cultivars by marker-assisted selection together with strategic deployment of these genes can be an important approach to develop stable resistance to BPH and sustain rice production in the tropical and temperate rice growing regions.